2007
DOI: 10.1007/s00428-007-0548-7
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of percutaneous organ biopsy as part of a minimally invasive perinatal autopsy

Abstract: To determine the feasibility of percutaneous fetal organ biopsies in the context of a 'minimally invasive' perinatal autopsy after stillbirth and termination for abnormality is the aim of this study. We assessed successful biopsy rate and the proportion adequate for histological examination in 30 fetuses undergoing organ sampling before autopsy. The relationship between gestational age, body weight, death-biopsy interval, operator experience and successful biopsy rate was investigated. Significant findings fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 18 publications
1
46
1
Order By: Relevance
“…The first study was of 30 neonatal cases that found adequate biopsy tissue was collected in 86% of lung and 76% of liver biopsies but in under 50% for other organs. 40 However, none of the histological abnormalities found during conventional autopsy were identified in the needle biopsy samples, i.e. the samples appeared to be adequate by volume but were non-diagnostic.…”
Section: Tissue Sampling Techniquesmentioning
confidence: 94%
See 1 more Smart Citation
“…The first study was of 30 neonatal cases that found adequate biopsy tissue was collected in 86% of lung and 76% of liver biopsies but in under 50% for other organs. 40 However, none of the histological abnormalities found during conventional autopsy were identified in the needle biopsy samples, i.e. the samples appeared to be adequate by volume but were non-diagnostic.…”
Section: Tissue Sampling Techniquesmentioning
confidence: 94%
“…the samples appeared to be adequate by volume but were non-diagnostic. 40 The second included 25 newborn infants and reported adequate tissue volumes collected for liver, lungs and brain biopsy in 92%, 84% and 68% of cases, respectively, but only 56%, 24% and 20% for right kidney, left kidney and spleen. 41 Final diagnosis could be made from the needle biopsy samples in 68% of cases with 56% full concordance with conventional autopsy.…”
Section: Tissue Sampling Techniquesmentioning
confidence: 99%
“…In the vast majority of cases, PIE affects premature, often low birth weight infants, who have primary surfactant deficiency and who are receiving mechanical ventilation [12,18,19]. In our study, cases with PIE were less in number to evaluate statistically.…”
Section: Discussionmentioning
confidence: 83%
“…In antepartum fetal death, histological abnormalities are most commonly found in the liver or lungs, for example, if showing evidence of fetal bacterial or viral infection [18]. In our cases, amnion aspiration was microscopically considered as similar to a lung of stillbirth which also expressed the collapse in alveoli.…”
Section: Discussionmentioning
confidence: 99%
“…However, the adequacy of such sampling in the postmortem setting has not yet been established, in particular regarding the potential issues of sample representativeness. In one study of 30 cases, PM needle biopsies were performed of major organs following PM MRI but not under direct MR image guidance, but representative and sufficient material was obtained in only 15 (50%; Breeze et al, 2008). A more practical effective alternative approach would be to perform PM imaging followed by endoscopic/laparoscopic direct organ visualization with biopsies carried out under direct vision, allowing macroscopic organ appearances to be determined in addition to providing larger biopsy samples.…”
Section: Lack Of Tissue Diagnosis/ancillary Investigations: Pm Image-mentioning
confidence: 99%